2014
DOI: 10.5505/jkartaltr.2014.07269
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Assessment and Level of Knowledge in Women With Low Levels of Education

Abstract: ÖzetAmaç: Otuz beş yaş ve üstü eğitim seviyesi düşük kadınların meme kanseri hakkında bilgilerini ölçmek, risk faktörlerini ortaya koymak ve risk hesaplaması yaparak kadınları bilgilendirmek.Gereç ve Yöntem: Sağlık Bakanlığı meme kanseri risk değerlendirme formu ve Gail modeli ile olguların risk oranları tespit edildi. Ayrıca kadınların meme muayenesi ve tarama hakkındaki bilgileri de kaydedildi. Bulgular:Olguların Gail modeliyle yapılan hesaplamasında yüksek risk saptanmadı. Sağlık Bakanlığı'nın risk değerlen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…While mentioning risk of breast cancer, it is required to consider the risk of breast cancer, which would emerge at a certain time, and have screenings according to age, which is the most important independent risk factor, since no risk factor is determined in majority of women with breast cancer. 19 It is indicated that the deaths caused by breast cancer, which kept increasing until 2000, have decreased in countries where the screenings are applied commonly and while the contribution of screenings is 2/3 in this decrease, the effect of developments in therapeutic methods is 1/3. 29 While early diagnosis is important in the treatment of breast cancer; numerous studies have showed that screening programs also have a positive contribution to the morbidity and mortality of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mentioning risk of breast cancer, it is required to consider the risk of breast cancer, which would emerge at a certain time, and have screenings according to age, which is the most important independent risk factor, since no risk factor is determined in majority of women with breast cancer. 19 It is indicated that the deaths caused by breast cancer, which kept increasing until 2000, have decreased in countries where the screenings are applied commonly and while the contribution of screenings is 2/3 in this decrease, the effect of developments in therapeutic methods is 1/3. 29 While early diagnosis is important in the treatment of breast cancer; numerous studies have showed that screening programs also have a positive contribution to the morbidity and mortality of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the data were collected by using data collection form, which was prepared by the researcher upon review of the relevant literatüre 1,7,16,19,20 …”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer is the most common cancer with a rate of 33% in female [1][2][3]. It accounts for 20% of cancer-related deaths and is the second most cause of cancer death in women all over the world [1,4]. The incidence of breast cancer varies between countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic characteristics (sex, race, age), reproductive history (menarche age, parturition, pregnancy age, breast-feeding history), familial-genetic factors (BRCA 1-2 gene mutation), environmental factors (radiotherapy story, hormone replacement therapy, alcohol consumption, socioeconomic level) have major effect [1,2]. The incidence of brest cancer in Turkey is reported as 35% based on data from the Ministry of Health [1,4]. As each country must do to reduce or even prevent the risk of breast cancer, we also need to determine the risk groups in Turkey and arrange the frequency of screening programs [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation